2015
DOI: 10.5455/jcer.201522
|View full text |Cite
|
Sign up to set email alerts
|

Prescription audit in the inpatients of a tertiary care hospital attached with medical college

Abstract: Background: Prescription audit is one of the methods to assess drug utilization and rationality of prescribing. Irrational prescribing is a worldwide problem. It is due to the faulty prescribing habits, lack of training amongst health care personnel, pressure from the pharmaceutical companies, and a lot of other reasons. Methods: The study was conducted by noting the details of patients admitted during 3 months from April to June 2015 in the Guru Gobind Singh Government Hospital, Jamnagar. Prescriptions were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…22 , Adama Hospital Medical College (96%) 16 and public health facilities in Maharashtra of India(100%) 19 . It is higher than the percentage of drugs prescribed by generic name in a study conducted at Jimma Hospital, south west Ethiopia, 75.2% 24 , Ayder hospital(83%) 15 , Eastern province, Saudi Arabia 61.2% 14 , Teaching hospital in North India, None is prescribed in generic name 18 , Garhwal (Uttaranchal), IndiaAbout 51% of the drugs were prescribed by generic names 20 , Tertiary care hospital (4.16%) Ambala, Haryana 12 . Such differences are due to prescribers interest toward brand prescription which is majorly expected to be due to promoters influence and increased number of seniour physicians.…”
Section: Resultsmentioning
confidence: 64%
“…22 , Adama Hospital Medical College (96%) 16 and public health facilities in Maharashtra of India(100%) 19 . It is higher than the percentage of drugs prescribed by generic name in a study conducted at Jimma Hospital, south west Ethiopia, 75.2% 24 , Ayder hospital(83%) 15 , Eastern province, Saudi Arabia 61.2% 14 , Teaching hospital in North India, None is prescribed in generic name 18 , Garhwal (Uttaranchal), IndiaAbout 51% of the drugs were prescribed by generic names 20 , Tertiary care hospital (4.16%) Ambala, Haryana 12 . Such differences are due to prescribers interest toward brand prescription which is majorly expected to be due to promoters influence and increased number of seniour physicians.…”
Section: Resultsmentioning
confidence: 64%
“…26 As far as dosage forms are concerned, oral dosage forms like tablets and capsules were the highest (64.16) which was comparable to a previous study done by Darji NH et al where the percentage of oral dosage forms was found to be 69.54%. 27 The ideal percentage of injections according to WHO must be between 13.4% to 24.1% but in our study it was found to be slightly higher 33.27% as our hospital was located in a rural part where the patients believe that always injection will be better than a tablet or capsule for any disease. Use of more number of injectable drugs was observed by Patel et al while some studies by Rehan et al reported use of less number of injectable drugs by interns in north India.…”
Section: Discussionmentioning
confidence: 64%
“…[6][7][8] This shows in our centre the number of drugs per prescription were rational when compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Antidiabetic drugs were 15.7%, 5.17, followed by antihypertensive drugs 15.7%, 7% and bronchodilators 13.16%, 10.31%. 8,10,11 Current study showed individual drugs prescribed for common conditions. Amlodipine 20%, 24% and 15%, Glimipiride 20%, 22%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation